METHODOLOGY OF TEACHING BIOPHYSICS BASED ON AN INNOVATIVE APPROACH - Z.M.Narzullayeva (TADQIQOTLAR, 2025)
Abstract. This in the article biophysics science innovative pedagogical technologies based on of teaching theoretical-methodical basics , interactive methods , digital education from the means use , in students research skills formation and interdisciplinary integration importance analysis Innovative approaches efficiency practical examples with based on is given .